Operational Costs of Unmanned Aircraft System for Applying Pesticides and Fertilizers - L. A. Marchenko; I. G. Smirnov; R. K. Kurbanov; A. Yu. Spiridonov (Сельскохозяйственные машины и технологии)
The calculation of aircraft cost is stated necessary to assess the economic feasibility of their operation, as well as in agriculture, the possibility of acquiring new ones, and to justify air transportation tariffs. (Research purpose) The research purpose is to substantiate the methodology and calculate the prime cost of using BAS-137 VIM unmanned aerial system for the application of pesticides, fertilizers and other agrochemicals. (Materials and methods) When developing the methodology for calculating the prime cost of using an unmanned aerial system for applying pesticides and fertilizers, the Guidelines for determining the cost of domestic and international flights for Russian airlines were used. (Results and discussion) We have obtained the main dependences of the prime cost of using BAS-137 VIM for the introduction of working fluids: on the application rate, the field rut length, the distance of approach to the refueling place, and the operating flight speed. (Conclusions) The authors developed a methodology for calculating the prime cost of using an unmanned aerial system for applying pesticides and fertilizers, including direct and indirect operating costs. It was found out that at the working fluid application rates of 5-100 liters per hectare, the changes in the cost of using BAS-137 VIM are within the range from 280.9 to 1315.5 rubles per hectare. At an application rate of 10 liters per hectare within the rut length of 0.3-2.0 kilometers, the application prime cost is 307.1-529.5 rubles per hectare. It was obtained that at the application rates of 5-20 liters per hectare and the rut length of 0.6-1.0 kilometers, the prime cost will be the lowest, within the range of 264-369 rubles per hectare at an operating flight speed of 60 kilometers per hour and within the range of 482-587 rubles per hectare at a flying speed of 30 kilometers per hour. It was shown that with a twofold increase in BAS-137 VIM operating speed, the prime cost decreases by 1.2-1.5 times.